Effect of Panpal pretreatment and antidotal treatment (HI-6 plus benactyzine) on respiratory and circulatory function in soman-poisoned rats - Kassa, J; Fusek, J (Human & experimental toxicology, 1997)
1 The effect of pharmacological pretreatment (pyridostigmine, benactyzine and trihexyphenidyle), designated Panpal, and antidotal treatment (the oxime HI-6 plus benactyzine) in soman poisoning was investigated in a rat model with on-line monitoring of respiratory and circulatory parameters. 2 Soman poisoning caused a high decrease in respiratory rate as well as minute respiratory volume and an increase in mean arterial pressure from 30-120 min following soman challenge. Soman at sublethal dose also significantly inhibited acetylcholinesterase activity in diaphragm and various brain parts. 3 Panpal pretreatment as well as antidotal treatment were effective in improving the respiratory and circulatory function disturbed by soman without the ability to increase significantly soman-inhibited acetylcholinesterase activity in all brain parts studied. 4 The efficacy of combined Panpal pretreatment and antidotal treatment against sublethal soman poisoning was not different from the efficacy of Panpal pretreatment or antidotal treatment alone. 5 The results of this investigation suggest that Panpal pretreatment as well as antidotal treatment are able to restore respiratory and circulatory function in soman-poisoned rats without significant reactivation of brain acetylcholinesterase.
Keywords: Animals; Acetylcholinesterase; Chemical Warfare Agents; antidota; Rats, Wistar; Benactyzine; benaktyzin; Central Nervous System Diseases; oximy; Pyridinium Compounds; pyridinové sloučeniny; Trihexyphenidyl; chemické bojové látky; Drug Therapy, Combination; Respiration; Antidotes; mozek; Electrocardiography; krevní tlak; elektrokardiografie; srdeční frekvence; Pyridostigmine Bromide; dýchání; Oximes; Male; pyridostigmin-bromid; Soman; acetylcholinesterasa; nemoci centrálního nervového systému; Brain; reaktivátory cholinesterasy; Diaphragm; kombinovaná farmakoterapie; soman; krysa rodu Rattus; trihexyfenidyl; zvířata; mužské pohlaví; cholinesterasové inhibitory; Blood Pressure; Cholinesterase Inhibitors; Heart Rate; Rats; bránice; Cholinesterase Reactivators; potkani Wistar